AKOMODASI HAK PEREMPUAN PADA IMPLEMENTASI PERATURAN KOMISI PEMILIHAN UMUM (PKPU) NO. 7 TAHUN 2013 DI KOTA PAREPARE - Abd. Rauf Ibrahim; Hasnani Hasnani; Nanning Nanning (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
This research studied about reviewing women's rights to the implementation of general election regulations (PKPU) No. 7 2013 in Parepare. It also studied about female candidates in fighting to be the list of legislative candidates. This study was conducted with qualitative research with a focus on case studies, using in-depth interview data and supporting data from KPU. The result of the study shows the regulations guarantee women's political rights, but still have hampering on implementations because of both cultural values ​​of society and technical constrains. Thus, the recommendations from the results of this study are (1) political parties must have a commitment in preparing their female cadres to fight on the legislative political stage. (2) An open proportional election system needs to be revised because it has an impact on the powerlessness of the party to carry out its qualified cadres who have no an established fund.